2010
DOI: 10.1002/chem.201002079
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Discrimination of Polycyclic Aromatic Hydrocarbon (PAH) Enantiomers on a Metal Surface

Abstract: Desymmetrization of diols is a powerful tool to the synthesis of chiral building blocks. Among the different approaches to perform discrimination between both enantiotopic hydroxyl groups, the organocatalytic approach has gained importance in the last years. A diverse range of organocatalysts has been used to efficiently promote this enantioselective transformation and this Minireview examines the different contributions in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(11 reference statements)
3
6
0
Order By: Relevance
“…However, the moleculeÀsubstrate interaction is not strong enough to disrupt the molecular structure. 29 Our calculations reproduce this experimental observation. We have found by density functional theory (DFT) that the precursor 4 adsorbs 0.31 nm above the surface by electrostatic interactions derived from vdW forces with a binding energy of 1.5 eV per molecule, which is high enough to prevent its diffusion.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…However, the moleculeÀsubstrate interaction is not strong enough to disrupt the molecular structure. 29 Our calculations reproduce this experimental observation. We have found by density functional theory (DFT) that the precursor 4 adsorbs 0.31 nm above the surface by electrostatic interactions derived from vdW forces with a binding energy of 1.5 eV per molecule, which is high enough to prevent its diffusion.…”
Section: Resultssupporting
confidence: 77%
“…We clearly distinguish in the STM images the shape of individual molecules and resolve the submolecular structure of 1 (in agreement with previous studies; 7 Figure 2a, inset) and 4 (Figure 2c, inset). 3,29 Upon annealing 1 and 4 on Pt(111) at about 720 K, they both change their shape, size, and intramolecular structure (Figure 2b and d). In the case of 1, its shape converts from triangular to spherical (2) (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…This value is compatible with the central aromatic ring in a parallel geometry to the surface, in agreement with other reported examples of related molecules like phenol, aniline or tetra-amino benzene on metallic surfaces [32–36]. Moreover, large polycyclic aromatic hydrocarbons (PAHs), mainly formed by benzene like rings have an apparent height of less than 2 Å in a planar configuration parallel to the surface [3,37]. At a first glance, the difference detected in the internal structure of the molecules could be ascribed to two different adsorption configurations on the Pt surface (a structural effect) and / or to a reorganization of the electronic structure due to a chemical change in the molecule.…”
Section: Resultssupporting
confidence: 90%
“…Thus, it has been recently shown that the interaction of a large PAH (C 60 H 30 ) with a Pt(111) surface can be rationalized by the interaction of the small benzene constituent subunits, which try to be adsorbed at specific surface positions leading to a deep energy adsorption minima for a particular orientation of the PAH on the surface. 24…”
Section: Importance Of the Metal Surfacesmentioning
confidence: 99%